Moral distress in workers Nursing of a philanthropic hospital (Research, Society and Development, 2020)
Aimed to investigate the frequency and intensity of moral distress in nursing workers in a philanthropic hospital. Cross-sectional study, carried out with 177 nursing workers from a philanthropic hospital. An instrument was used with data sociodemographic, labor and the scale Moral Distress Scale-Revised. For data analysis, descriptive statistics were used. The average intensity of moral distress experienced by the nursing team ranged from 1.32 to 2.12, while the frequency varied from 0.52 to 2.08. Higher averages were evidenced in situations that involved following the family's wishes to maintain life and therapeutic obstinacy. Global moral distress had an average frequency and intensity of 67.83. It is concluded that nursing workers presented low to moderate moral distress.